2020
DOI: 10.2166/wst.2020.558
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalising wastewater surveillance systems to minimise the impact of COVID-19: cases of Indonesia, Japan and Viet Nam

Abstract: This mini review describes the current status and challenges regarding institutionalisation of wastewater surveillance systems against COVID-19. Monitoring SARS-CoV-2 in wastewater has been proposed to be a potential tool to understand the actual prevalence of COVID-19 in the community, and it could be an effective approach to monitor the trend during the COVID-19 pandemic. However, challenges to institutionalise wastewater surveillance systems are still abundant and unfolding at a rapid rate given that the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Alongside high interest in the ES of SARS-CoV-2 as a means to manage COVID-19 outbreaks, the performance of such surveillance has been systematically reviewed, with findings suggesting that positive signals typically anticipate clinically confirmed cases by a minimum of 10 days (Shah et al 2022). The implementation and institutionalising of ES have also been discussed, and the importance of bringing together stakeholders to support public health decisions has been highlighted (Medema et al 2020a;Takeda et al 2021). In addition, the terms used for ES have been reviewed, due to the lack of a common terminology (Larsen et al 2021).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…Alongside high interest in the ES of SARS-CoV-2 as a means to manage COVID-19 outbreaks, the performance of such surveillance has been systematically reviewed, with findings suggesting that positive signals typically anticipate clinically confirmed cases by a minimum of 10 days (Shah et al 2022). The implementation and institutionalising of ES have also been discussed, and the importance of bringing together stakeholders to support public health decisions has been highlighted (Medema et al 2020a;Takeda et al 2021). In addition, the terms used for ES have been reviewed, due to the lack of a common terminology (Larsen et al 2021).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…Since the start of the pandemic, many groups have worked on wastewater-based surveillance methods, using various ways of communicating their findings to diverse groups of stakeholders, describing logistical challenges for WBE in Africa, the Netherlands, Turkey and England [ 71 ]. Takeda et al (2021) [ 72 ] described the development and challenges in Indonesia, Japan and Vietnam and Wade et al (2022) discussed lessons learnt from the UK. A dashboard of daily frequencies seems to be the most common approach for real-time documentation and communication of the state of the epidemic; see Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that COVID-19 wastewater-based epidemiological approaches provide indirect information about the burden of COVID-19 in a defined community [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The approach provides a proxy indicator for the concentration of RNA shed by infected individuals at different stages of the disease, including even pre-symptomatic and asymptomatic cases [ 38 ]. Accordingly, an increase or a decrease in wastewater viral concentration can be inferred to the number of new or resolved SARS-CoV-2 infections in the community.…”
Section: Discussionmentioning
confidence: 99%